Scientific knowledge and attitude change: The impact of a citizen science project - Brossard, Dominique; Lewenstein, Bruce; Bonney, Rick (International journal of science education, 2005)
This paper discusses the evaluation of an informal science education project, The Birdhouse Network (TBN) of the Cornell Laboratory of Ornithology. The Elaboration Likelihood Model and the theory of Experiential Education were used as frameworks to analyse the impact of TBN on participants' attitudes toward science and the environment, on their knowledge of bird biology, and on their understanding of the scientific process. The project had an impact on participants' knowledge of bird biology. No statistically significant change in participants' attitudes toward science or the environment, or in participants' understanding of the scientific process, could be detected. The results suggest that projects must make explicit to participants the issues that they are experiencing. In addition, the results suggest that more sensitive measures need to be designed to assess attitude change among environmentally aware citizens.